Polymer bilayers with enhanced dielectric permittivity and low dielectric losses by Maxwell–Wagner–Sillars interfacial polarization: Characteristic frequencies and scaling laws. Issue 22 (6th February 2019) - Samet, M.; Kallel, A.; Serghei, A.
ABSTRACT: An efficient approach to obtain polymeric materials with high permittivity values and low dielectric losses is presented in the current study. For this purpose, dielectric measurements by means of broadband dielectric spectroscopy, numerical simulations, and analytical calculations have been carried out for bilayer structures consisting in an insulating and a conductive polymer layer. Polyethyleneterephtalate and polytetrafluoroethylene have been used as insulating layers while, as conductive materials, blends of polyvinyl acetate with an ionic liquid, 1‐butyl‐3‐methylimidazolium tetrafluoroborate. The dielectric properties of the samples have been investigated in a broad frequency (from 10 −1 to 10 7 Hz) and temperature range in order to determine, through the analysis of the scaling laws governing the interfacial polarization effects, the characteristic frequency ranges and the amplitude of the enhanced permittivity. An excellent agreement is found between the experimental results, the numerical simulations, and the analytical calculations. Finally, we show that bilayer polymeric materials with permittivity values as high as ε ′ = 556 and with low dielectric losses (tan( δ ) = 0.001) can be readily obtained by the current approach. This could have multiple applications, especially in the field of organic electronics. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47551. Abstract :